A review of the known distribution of Halophila spinulosa in Indonesia with herbarium from Laikang in South Sulawesi. Issue 1 (May 2021) - Yasir, I; Moore, A M
Abstract: Seagrasses are true plants living in the marine realm. The Coral Triangle is also the centre of seagrass diversity with 14 species recorded in Indonesian waters. There is a growing awareness of the ecological and socio-economic importance of seagrass meadows as well as the growing threats to these valuable coastal ecosystems. However, there is a lack of accessible data on seagrass distribution at ecosystem and species scales. The most speciose seagrass genus is Halophila, with at least 7 species ( Halophila beccarii, H. decipiens, H. major, H. minor, H. ovalis, H. sulawesii and H. spinulosa ) known to occur in Indonesia. Reported from Malaysia to eastern Australia, Halophila spinulosa is a data deficient tropical seagrass. We review the known distribution of H. spinulosa based on a search of Indonesian and international literature. We also present an annotated herbarium of H. spinulosa samples collected from Laikang in South Sulawesi, Indonesia. Samples were collected in September 2020 at low tide at depths of around 0.75 to 1.25 m on a silty sand substrate along with samples of other seagrass species present. Herbarium specimens were cleaned of epiphytes and sand. The samples were laid out carefully on A4 paper, arranged so that all parts were clearly visible, covered with gauze, and placed on folded newspaper. The prepared samples were then sandwiched between piles of newspaper and placed in a wooden press. The herbarium specimens will be preserved in the Marine Biology Laboratory collection, Marine Science Department, Universitas Hasanuddin. We consider the distribution data for H spinulosa are far from complete; this review and herbarium should inform and spur further research on this species and it's distribution at macro (site) and micro (within site) scales.